Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevc.84.044908
|View full text |Cite
|
Sign up to set email alerts
|

Quarkonium dissociation in quark-gluon plasma via ionization in a magnetic field

Abstract: We study the impact of a magnetic field, generated in collisions of relativistic heavy ions, on the decay probability of a quarkonium produced in the central rapidity region. The quark and antiquark components are subject to mutually orthogonal electric and magnetic fields in the quarkonium comoving frame. In the presence of an electric field, the quarkonium has a finite dissociation probability.We use theWKB approximation to derive the dissociation probability. We find that the quarkonium dissociation energy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 67 publications
1
84
0
1
Order By: Relevance
“…In particular, when j = k, ω s,jk = 0, i.e. no photon is emitted, which is also evident in (10). The reason is clearly seen in the frame where p = 0: since ε j ≥ ε k , constraints (2) and (3) hold only if ω = 0.…”
Section: Synchrotron Radiationmentioning
confidence: 69%
See 1 more Smart Citation
“…In particular, when j = k, ω s,jk = 0, i.e. no photon is emitted, which is also evident in (10). The reason is clearly seen in the frame where p = 0: since ε j ≥ ε k , constraints (2) and (3) hold only if ω = 0.…”
Section: Synchrotron Radiationmentioning
confidence: 69%
“…It contributes to enhancement of dilepton production at low invariant masses [7] and enhances the azimuthal anisotropy of the quark-gluon plasma (QGP) [8,9]. It causes dissociation of the bound states, particularly charmonia, via ionization [10,11]. Additionally, magnetic field may drive the Chiral Magnetic Effect (CME) [1,12], which is the generation of an electric field parallel to the magnetic one via the axial anomaly in the hot nuclear matter.…”
Section: Introductionmentioning
confidence: 99%
“…possible ρ meson condensation in strong magnetic field [50][51][52][53][54], the neutral pion condensation in vaccum [55], the anisotropic viscosities in hydrodynamic equations [56][57][58][59][60], and the early-stage phenomena in heavy-ion collisions like the EM-field induced particle production [26,[61][62][63][64][65][66] and the dissociation of heavy-flavor mesons [67][68][69][70][71]. These topics will not be the main focus of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by formation of strong electromagnetic fields in neutron stars/magnetars [3,4] and ultrarelativistic heavy-ion collisions at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC) [5][6][7][8], a number of lattice QCD simulations and analytic calculations have shown that strong magnetic fields modify properties of QCD vacuum such as quark condensates [5,[9][10][11][12][13][14][15][16][17][18] and gluon condensates [19,20], and consequently modify even phase structures [15,19,[21][22][23] and hadron properties [5,9,[24][25][26][27][28][29][30][31][32][33][34][35]. One of the remarkable findings is a discrepancy between meson spectra obtained from a hadronic effective model calculation and a lattice QCD simulation in strong magnetic fields [26,27].…”
Section: Introductionmentioning
confidence: 99%